The Role of Adult Education in Social Change: A Critical Review of Stephen Brookfield’s Scholarship - Mas'ud, Bulqia; Imansari, Nurul (Jurnal Ilmiah Mandala Education (JIME), 2022)
The purpose of this study is to understand the role of adult education in social change based on Stephen Brookfield’s scholarship. A critical review is done to analyze Brookfield’s thoughts and views about adult education. After reviewing four articles written by Brookfield, we found that there are three main roles of adult education formulated by Brookfield. First, adult education takes a role in social justice; second, adult education takes a role in social and political change, and third, adult education plays a role in social and community development. Besides, we also discuss the tradition of Brookfield scholarship which is mainly influenced by Marxism and understanding his identity as white Englishman and neutral academician who defends voices of marginal people rooted from his rich experiences work with minority group. Last, we bring up the educational practices suggested from Brookfield’s that views education related to social responsibility and policy which is not merely about teaching practice in classrooms. It is more a practical and critical education agenda that can solve public and social problem which inform policy making and concern on social injustice in the community.